2012
DOI: 10.1111/j.1468-2435.2008.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Making a living at the interface of legality and illegality: Chinese migrant workers in Israel1

Abstract: Since the late 1990s, Israel has become a new destination for Chinese migrant workers. In the view of many studies conducted in Israel, the Chinese migrant workers are often a neglected and almost invisible group. The purpose of this paper is to explore the initiation of this migration trend and its social consequences. The major discussion of this study focuses on how the whole process of migration is carried out at the interface between legality and illegality. Research in the sending area suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In Japan, G. Liu-Farrer (2008) argued that the social capital that initially facilitates migration, and which subsequently secures the livelihood of Fujian migrants, could ultimately become a liability prohibiting them from achieving upward mobility. Finally, Minghuan (2012) explored both the commencement and consequences of Fujian immigration in Israel. Like Kwong, she suggested that both documented and undocumented migrant workers from Fujian serve the urgent need for manual labour, and in the process turn the transnational transportation of labour into a profitable business.…”
Section: The Impact Fujian Immigrants Have Exerted On Receiving Countmentioning
confidence: 99%
“…In Japan, G. Liu-Farrer (2008) argued that the social capital that initially facilitates migration, and which subsequently secures the livelihood of Fujian migrants, could ultimately become a liability prohibiting them from achieving upward mobility. Finally, Minghuan (2012) explored both the commencement and consequences of Fujian immigration in Israel. Like Kwong, she suggested that both documented and undocumented migrant workers from Fujian serve the urgent need for manual labour, and in the process turn the transnational transportation of labour into a profitable business.…”
Section: The Impact Fujian Immigrants Have Exerted On Receiving Countmentioning
confidence: 99%
“…According to the US Department of State Trafficking in Persons report (Nathan, ), the fees in Israel range from $1,000 to $10,000 for all workers except Chinese workers who pay up to $20,000. Minghuan () found that Chinese construction workers pay sums that can reach up to $18,750.…”
Section: Brokerage Fees In Israelmentioning
confidence: 99%
“…The shift to a largely market-driven system of labor migrant recruitment fomented the proliferation of a large industry of private agents and intermediaries (Ellman, 2003;Agunias, 2009;Minghuan, 2012;Fernandez, 2013). The shift to a largely market-driven system of labor migrant recruitment fomented the proliferation of a large industry of private agents and intermediaries (Ellman, 2003;Agunias, 2009;Minghuan, 2012;Fernandez, 2013).…”
Section: Precarious Character Of Migrant Labor: Intersection Of Rightmentioning
confidence: 99%
“…2003; Kushnirovich, 2010), rights abuses (Willen, 2003), and non-appropriate living conditions (Minghuan, 2012), which became widespread in Israel in the 2000s (Gottlieb, 2002;Ellman, 2003).…”
Section: The Construction Sectormentioning
confidence: 99%
See 1 more Smart Citation